Identification of signature volatiles to discriminate Candida albicans, glabrata, krusei and tropicalis using gas chromatography and mass spectrometry. Issue 2 (14th December 2015) - Hertel, Moritz; Hartwig, Stefan; Schütte, Eyke; Gillissen, Bernhard; Preissner, Robert; Schmidt‐Westhausen, Andrea Maria; Paris, Sebastian; Kastner, Isabell; Preissner, Saskia
Summary: Oral candidiasis is the most frequent fungal infection of the oral cavity. Clinical diagnoses require mycological confirmation, which is time‐consuming in case of culture testing. The aim of the study was to identify signature volatiles to develop a chairside breath test to diagnose oral candidiasis. Headspaces above Candida albicans, glabrata, tropicalis, krusei cultures, and growth media as control were analysed after eight and 24 h using offline gas chromatography and mass spectrometry. The identification of signature volatiles was assisted using various microbial databases. Retrieved volatile patterns enabled Candida species discrimination in vitro . For C. albicans 3‐methyl‐2‐butanone and styrene and for C. krusei a combination of p‐xylene, 2‐octanone, 2‐heptanone and n‐butyl acetate were found to be specific. 1‐hexanol was found in C. tropicalis, but is emitted by a variety of other microorganisms. C. glabrata was characterised through the absence of these volatiles. The development of a breath test is a promising approach in confirming suspicions of oral candidiasis. To confirm the retrieved results in vivo, breath tests in affected and healthy subjects have to be performed.